Ionic and stable isotope chemistry as indicators of water sources to the Upper Mendoza River basin, Central Andes of Argentina. Issue 4 (12th March 2017) - Crespo, S.; Aranibar, J.; Gomez, L.; Schwikowski, M.; Bruetsch, S.; Cara, L.; Villalba, R.
ABSTRACT: The Mendoza River is mainly dependent on the melting of snow and ice in the Upper Andes. Since predicted changes in climate would modify snow accumulation and glacial melting, it is important to understand the relative contributions of various water sources to river discharge. The two main mountain ranges in the basin, Cordillera Principal and Cordillera Frontal, present differences in geology and receive differing proportions of precipitation from Atlantic and Pacific moisture sources. We propose that differences in the origin of precipitation, geology and sediment contact times across the basin generate ionic and stable isotopic signatures in the water, allowing the differentiation of water sources. Waters from the Cordillera Principal had higher salinity and were more isotopically depleted than those from the Cordillera Frontal. Stable isotope composition and salinity differed among different water sources. The chemical temporal evolution of rivers and streams indicated changes in the relative contributions of different sources, pointing to the importance of glacier melting and groundwater in the river discharge.